Inoculation of Burkholderia cepacia and Gluconacetobacter diazotrophicus on phenotype and biomass of Triticum aestivum var. Nana-F2007 at 50% of nitrogen fertilizer (Scientia Agropecuaria, 2015)
Wheat (Triticum aestivum L) consuming requires of nitrogen fertilizer (NF), as ammonium nitrate (NH4NO3), which one in excess causes lost soil productivity. An alternative to reduce and optimize NF to wheat is to inoculate with endophytic promoting growth bacteria (EPGB), as genus Burkholderia cepacia and Gluconacetobacter diazotrophicus able to improve radical uptake of NF, its suggesting by inducing synthesis of growth promoting vegetal substances (GPVS). The aim of this research was to evaluate the inoculation of Burkholderia cepacia and Gluconacetobacter diazotrophicus on phenology and biomass of T. aestivum at 50% dose of NF. A trial in greenhouse condition was conducted inoculating seed T. aestivum´s with both EPGB by measuring its phenology: (PH) plant height, (RL) root length and biomass: total fresh weight (TFW) and dry (TDW) at seedling and flowering stages. Results showed a positive effect of B. cepacia in wheat on its TDW with 0.61g value statistically significant compared to 0.53g TDW of wheat used as relative control fed with NF 100% dose (RC). B. cepacia and G. diazotrophicus inoculated to wheat had a positive increased on its TDW with 4.23 g value statistically significant compared to 1.13 g TDW of wheat used as RC. Conclusion suggested that B. cepacia and G. diazotrophicus by synthetized GPVS had a positive effect on wheat growth at reduced dose of NF.
Keywords: xylem colonization; rhizosphere; synergism; radical uptake